Adam Smith: Left or Right?. (8th October 2012) - Smith, Craig
Abstract : This article engages with some of the recent literature on Adam Smith which has sought to distance the 'father of economics' from his contemporary free market admirers and to reclaim him as a hero and inspiration for the political left. The article explores a problem for this attempted recovery of Smith by the contemporary social democrat which arises from his strictly negative understanding of the virtue of justice. I argue that Smith's distinctions between justice, benevolence and 'police' should be taken seriously as an attempt at introducing conceptual clarity into the terminology of political theory. The article makes the case for reading Smith as someone who quite explicitly rejects the notion of regarding our obligations to the poor in terms of justice and whose distinctly sceptical view of politics makes him an unlikely inspiration for contemporary philosophers concerned with developing normative notions of social justice intended to justify the redistribution of wealth.